Effect of varying stocking densities on the production attributes of Climbing Perch (Anabas testudineus) in a cage culture environment: Cage culture of climbing perch - Debnath, Chandan; Kumar Das, Sanjay; Mahanta, Prasanta (Journal of the Inland Fisheries Society of India, 2023)
Anabas testudineus (Climbing perch) growth and production were estimated using locally constructed cages (1 m3) at various stocking densities (40, 60, 80 and 100 fish m-3) in a forest water body, located in Tripura, NE India. Each rearing density was repeated three times. The size of the fish at release was 3.5 ± 0.3 cm/2.8 ± 0.35 g and they fed with pellet feed @ 2% (28% CP) of fish biomass. After 180 days of farming, we observed that an increase in stocking density decreased fish length, body weight, specific growth rate (SGR) and survival rate, as well as reduced feed conversion efficiency of fish. Maximum fish growth was recorded at a stocking density of 40 fish m-3 (84.5 ± 0.67 g fish-1) and minimum at density of 100 fish m-3 (53.4 ± 3.07 g fish-1). There was no significant difference in weight gain and SGR between 40 and 60 fish m-3 (p 0.05). The SGR ranged from 1.63 to 1.88%/ day and the FCR ranged from 2.3 to 2.8. Survival was highest at 40 fish m-3 (87.6%) and lowest at 100 fish m-3 (58.6%). Fish biomass production ranged from 2.96 ± 0.05 kg (40 fish m-3) to 4.0 ± 0.29 kg cage-1 (60 fish m-3). Based on this study, it can be concluded that a stocking density of 60 fish m-3 is optimal for cage farming of A. testudineus to ensure better growth and survival of the fish and forest water bodies can be explored for cage culture.